GEGURITAN KONTABOJA: ANALISIS STRUKTUR DAN MAKNA - Purnama Wulandari, Ida Ayu Eka (Humanis, 2016)
This study discusses about Geguritan Kontaboja with strcture analysis and meaning. The aim of this study is to reveal the structure that form the literature and to exhibit the implicit meaning. The theory used in this study is structural theory proposed by Teeuw while the Semiotical theory proposed by Charles Pierce. Therefore, the analysis of Geguritan Kontaboja will be able to be realised. Methode and technique used in this study were devided into three phases: (1) methode and technique of providing data used reading, recording, and translating technique, (2) qualitative methode used in methode and technique of analyzing data, (3) methode and technique of presenting data used formal and informal methode which are asissted by deductive and inductive technique. The result of this study are forma structure consists of: literature and language code, language style, language variety. Narative structure consists of: incident, plot, character and characteriations, setting, theme, and moral value. Besides, this study also aims to reveal the implicit meaning of Geguritan Kontaboja that is consists of: loyalty, matchmaking, inheritance, an the sense of name
Keywords: geguritan, structure, meaning